Implementasi Pendekatan Pembelajaran Culturally Responsive Teaching (Crt) untuk Meningkatkan Hasil Belajar Siswa di Kelas IV SDN 6 Cakranegara - firdha, Firdha; Tahir, M.; Herawati, Sri (Mataram University, 2025)
This classroom action research aims to improve the learning outcomes of fourth-grade students through the implementation of the Culturally Responsive Teaching (CRT) approach. The purpose of this study is to enhance students’ learning achievement by applying the CRT approach in class IV at SDN 6 Cakranegara. This research is a form of Classroom Action Research (CAR) conducted with the assistance of the classroom teacher as a collaborator. The study was carried out in two cycles, each consisting of two meetings. The subjects of this study were 20 fourth-grade students of SDN 6 Cakranegara. Data were collected through tests and observations, and analyzed descriptively using percentages. The results of the study showed an improvement in students’ learning outcomes following the implementation of the Culturally Responsive Teaching approach. This is evidenced by a learning achievement score of 0.93, categorized as high. The average learning outcomes of students before the implementation were in the low category. The average percentage of students’ learning motivation during the first cycle reached 0.63 (medium category), and increased to 0.92 (high category) in the second cycle. Observations also indicated that students became more persistent in completing tasks, resilient when facing difficulties, demonstrated high learning interest, enjoyed working independently, were able to defend their opinions, and showed enthusiasm in solving problems related to the learning materials.